Organoleptic Test of Chicken Sausage Made from Mocaf with The Addition of Moringa Leaves (Moringa oleifera) - Ma'ruf, Imam; Chusnah, MIftachul; Hartanti, Dyah Ayu Sri (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
This study aims to analyze the effect of adding moringa leaf extract (Moringa oleifera) on the organoleptic characteristics of chicken sausages based on mocaf flour (Modified Cassava Flour). The research design used was a Completely Randomized Design (CRD) with three treatments: the addition of 5 gr (P1), 10 gr (P2), and 15 gr (P3) of moringa leaf extract, each with three replications. The research method used in this study was descriptive qualitative which was continued with ANOVA test and 5% BNT test. The results showed that treatment P2 (10 gr) produced the highest score on all organoleptic parameters. The color of the sausage looks more attractive, the aroma is fresher, the most preferred taste, and the texture is chewy and soft. Meanwhile, P3 produces a color that is too thick and the aroma tends to be unpleasant so it is less preferred. P1 showed quite good results but not optimal. Based on these results, the addition of 10 gr of moringa leaf extract is the best formulation to improve the sensory quality of mocaf chicken sausages and has the potential as an innovation in functional food products accepted by consumers.